Smart Materials for Dynamic Thermal Radiation Regulation. Issue 35 (20th May 2021) - Wei, Hang; Gu, Jinxin; Ren, Feifei; Zhang, Leipeng; Xu, Gaoping; Wang, Bo; Song, Shanshan; Zhao, Jiupeng; Dou, Shuliang; Li, Yao
Abstract: Thermal radiation in the mid‐infrared region profoundly affects human lives in various fields, including thermal management, imaging, sensing, camouflage, and thermography. Due to their fixed emissivities, radiance features of conventional materials are usually proportional to the quadruplicate of surface temperature, which set the limit, that one type of material can only present a single thermal function. Therefore, it is necessary and urgent to design materials for dynamic thermal radiation regulations to fulfill the demands of the age of intelligent machines. Recently, the ability of some smart materials to dynamically regulate thermal radiation has been evaluated. These materials are found to be competent enough for various commands, thereby, providing better alternatives and tremendously promoting the commercial potentials. In this review, the dynamic regulatory mechanisms and recent progress in the evaluation of these smart materials are summarized, including thermochromic materials, electrochromic materials, mechanically and humidity responsive materials, with the potential applications, insufficient problems, and possible strategies highlighted. Abstract : Thermal radiation in the mid‐infrared region profoundly affects human lives. Conventional materials have fixed radiance features but, to fulfill the increasing demands of the age of intelligent machines, it is necessary and urgent to design smart materials for dynamic thermal radiation regulations. A systematic perspective of these materials is provided, stimulating new ideas and promoting progress of thermal regulation fields.